Cross-Generation Analysis of e-Book Consumers' Preferences-A Prerequisite for Effective Management of Public Library - Prokop, Viktor; Stejskal, Jan (MDPI, 2020)
Nowadays, with the growing importance of providing digital services, public libraries offer a wide range of e-books. However, current studies show that reading preferences vary across countries, and identifying e-book demand is therefore difficult. For these reasons, this article focuses on different groups of e-book readers (pensioners, students, economically active) and on factors affecting their attitude to reading e-books, willingness to receive new library services and willingness to pay for them. For the purpose of this analysis, we are using unique data from an online questionnaire survey among readers of the Municipal Library of Prague in 2019 and own binary logistic models. The results show how e-book genres, information preferences and devices for reading e-books primarily affect selected groups of e-book readers. The unwillingness of e-book readers to pay for library services is also evident, especially among students. In the last section, we propose some practical implications that could help to library management and possibly attract more e-book readers from different groups.
Analýza mezigeneračních preferencí uživatelů knihovnických služeb - předpoklad efektivního managementu veřejného knihovny
Keywords: library; e-books; customer preferences; cross-generation analysis; knihovny; e-knihy; preference zákazníků; mezigenerační analýza